Effect of adding sawdust and husk ash on N, P, K and C-organic content in making goat manure compost - Ely Vebriyanti; Boni Qarahma; Deni Novia (Fakultas Pertanian Universitas Majalengka, 2024)
This research aims to determine the effect of adding sawdust and husk ash on the N, P, K and C-Organic content in making goat manure compost. Materials used in making compost include: sawdust, husk ash, goat manure, EM4, water and palm sugar. This research was conducted using the Completely Randomized Design (CRD) method consisting of 5 treatments and 4 replications. The percentage ratio of goat manure, sawdust, and husk ash used in each treatment is A (100:0), B (75:25), C (75:25), D (75:12.5:12.5) and E (50:25:25). The variables observed were levels of N, P, K, and C-Organic. The data obtained were analyzed using the F test, followed by Duncan's Multiple Range Test (DMRT) with a 95% confident level. The result shows that the addition of sawdust and husk ash to composting goat manure had no significant effect (p>0.05) on the N, P and K content, but had a significant effect (p<0.05) on organic C. It can be concluded that Compost with the addition of sawdust and husk ash in compost has no significant effect (p>0.05) on the N, P, and K content but has a significant effect (p<0.05) on the organic C. Based on the results of research that has been carried out regarding the addition of sawdust and husk ash to making goat manure compost, it was found that the chemical parameters of the compost in the form of Nitrogen, Phosphorus, Potassium, and C-organic are by SNI 19-7030-2024.